2022
DOI: 10.1164/rccm.202109-2079pp
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive Afterload Lowering to Improve the Right Ventricle: A New Target for Medical Therapy in Pulmonary Arterial Hypertension?

Abstract: Despite numerous therapeutic advances in pulmonary arterial hypertension, patients continue to suffer high morbidity and mortality, particularly considering a median age of 50 years. This article explores whether early, robust reduction of right ventricular afterload would facilitate substantial improvement in right ventricular function and thus whether afterload reduction should be a treatment goal for pulmonary arterial hypertension. The earliest clinical studies of prostanoid treatment in pulmonary arterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 74 publications
0
43
0
1
Order By: Relevance
“…Althought some discussion still persists on the opportunity of an initial combination therapy for those patients with cardiovascular risk factors (21), we observed that a not negligible proportion of patients with one comorbidity showed a considerable hemodynamic and clinical response to therapy, as 25% of patients had more than 51% reduction in PVR and up to 35% of patients achieved a low risk status. The importance of PVR reduction has been recently recognized by increasing evidence showing that a significant decrease in PVR is needed to induce RV reverse remodeling and functional recovery (14,(22)(23)(24)(25)(26)(27)(28). Patients with > 1 cardiovascular comorbidity showed a less important reduction in PVR associated with a higher proportion of RV dilation and severe tricuspid regurgitation compared with the others.…”
Section: Discussionmentioning
confidence: 99%
“…Althought some discussion still persists on the opportunity of an initial combination therapy for those patients with cardiovascular risk factors (21), we observed that a not negligible proportion of patients with one comorbidity showed a considerable hemodynamic and clinical response to therapy, as 25% of patients had more than 51% reduction in PVR and up to 35% of patients achieved a low risk status. The importance of PVR reduction has been recently recognized by increasing evidence showing that a significant decrease in PVR is needed to induce RV reverse remodeling and functional recovery (14,(22)(23)(24)(25)(26)(27)(28). Patients with > 1 cardiovascular comorbidity showed a less important reduction in PVR associated with a higher proportion of RV dilation and severe tricuspid regurgitation compared with the others.…”
Section: Discussionmentioning
confidence: 99%
“…Initial combination therapy, including parenteral prostacyclins, is associated with a greater RHRR than with other treatment strategies and specifically, more than 50% of RHRR was obtained with >50% reduction in PVR [26]. All data verify that robust hemodynamic improvements can reverse pathologic remodeling of the right ventricle and restore RV function to normal in PAH [18], so if normal RV function were the goal of treatment during patients' follow-up, the prognosis could be better.…”
Section: Pah Risk Stratificationmentioning
confidence: 74%
“…Right Heart Catheterization represents an accurate monitoring strategy and Cardiac Index is the first parameter associated to survival, reflecting indirectly RV function, already used in risk stratification assessment according to Guidelines. Interestingly, RV afterload reduction is not recommended to be the treatment goal, even though numerous studies suggest that greater RV afterload reduction leads to a profound reverse RV remodelling improving RV function and prognosis [18]. However, reaching threshold levels for pulmonary arterial pressure or vascular resistance seems to play pivotal role in interrupting the self-perpetuating injury of pulmonary vascular disease.…”
Section: Pah Risk Stratificationmentioning
confidence: 99%
See 1 more Smart Citation
“…With disease that may not be completely addressed by oral or inhaled therapies, parenteral therapy is warranted. Newer guidelines are driven primarily by patient risk stratification, and combination and escalation therapy is often recommended if low-risk status is not achieved ( 14 , 15 ). This approach may not account for a patient’s perspective or the impact of multiple therapies on HRQOL.…”
mentioning
confidence: 99%